Veredas, oásis do sertão: conflito ambiental na apropriação das águas em Botumirim - MG / Veredas, oasis of Sertão: environmental conflict in Botumirim, Minas Gerais (Brazil) - Leila Ribeiro Rodrigues; Ana Paula Glinfskoi Thé (Sociedade & Natureza)
This paper describes an ethnographic research which aimed at analyzing the influence of traditional water resource use and management as well as its role in the process of building community identities and territorialities. Furthermore, the paper analyses the environmental conflicts associated with the dispute between the community’s traditional way of life and governmental policies towards environmental conservation. The research was carried out in the Gigante and Pé da Serra community, within the municipality of Botumirim, in the region recognized as Vale do Jequitinhonha, Minas Gerais State. The community’s livelihood and means of existence are related to familiar agriculture, having values and rules linked to a specific traditional culture, in which water has significant importance. This area and its water resources have been disputed by different types users and institutions with very different interests and economic power, setting traditional communities, their means of existence, their culture and their common use of natural resources at risk.